2010
DOI: 10.1007/s13312-010-0156-5
|View full text |Cite
|
Sign up to set email alerts
|

School absenteeism among children and its correlates: A predictive model for identifying absentees

Abstract: it is possible to identify potential absentees in school children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 15 publications
3
12
1
Order By: Relevance
“…Although numerical definition of absenteeism varies, the broad concept of absenteeism has been consistent, defined as the total number of absent days from school from the total number of available school days of a calendar year [11,37,38]. In our study, absenteeism, defined as non-attendance on at least 20% of school days, as recorded by the school, was present in 26.8% of the sample.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Although numerical definition of absenteeism varies, the broad concept of absenteeism has been consistent, defined as the total number of absent days from school from the total number of available school days of a calendar year [11,37,38]. In our study, absenteeism, defined as non-attendance on at least 20% of school days, as recorded by the school, was present in 26.8% of the sample.…”
Section: Discussionmentioning
confidence: 66%
“…There is no consensus definition of significant absenteeism to our knowledge, and it varies according to the cut-off points applied by different authors [11,12,37,38]. Although numerical definition of absenteeism varies, the broad concept of absenteeism has been consistent, defined as the total number of absent days from school from the total number of available school days of a calendar year [11,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…In Delhi, 48% children were absent for more than 2 days per month on an average. [9] In a study conducted in the US reported -11% were absent for 1 to 3 days and 2% of student were absent for 4 or more days in past 30 days. [14] This study showed illness, unfavorable weather condition, and social or family occasions were the most frequent causes of school absenteeism during the mentioned study period.…”
Section: Discussionmentioning
confidence: 98%
“…Severely ill, and those who refused to participate were excluded from the study. Now, considering estimated prevalence of 48% [9] and with 10% absolute error, the sample size calculated was 96 after applying the formula -sample size = Z α/2 2 PQ/d 2 (here P [prevalence] = 0.48; Q = [1-P] = 0.52; d = allowable error). With a design effect of 2, the final sample size calculated was 192.…”
Section: Study Populationmentioning
confidence: 99%
“…We use the term sick days for the findings, because absenteeism may have a broader meaning beyond sickness; even though absenteeism and sick leave in the context of school children is used interchangeably by many authors. While school absenteeism has been studied elsewhere from different perspectives [4], information about health-related absenteeism in primary school children is limited. Some authors found associations of body mass index and obesity with school absenteeism, but results are not consistent [510].…”
Section: Introductionmentioning
confidence: 99%